Migration and access to health services: the case of Mexican population living in Minnesota, USA - Pardo Montaño, Ana Melisa (2016)
The objective of this research is to give a general view of access to health services of Mexican immigrants in the United States (US), particularly in Minnesota. In the introduction we present general data regarding Mexican population living in the US and Minnesota, we also examine this population’s access to health insurance and use of health services in the US. Further on, we analyze the particular case of Mexican population living in Minnesota and their access to health services, and we mention some mechanisms through which migrants can have to use health services. The information was obtained from the most recent statistics presented by the Consejo Nacional de Población (Mexico), the National Health Interview Survey (2009-2011) and the National Healthcare Disparities Report (2012). Interviews in Minnesota were carried out, both with migrants and representatives of migrant organizations which provide assistance to this population.